2012
DOI: 10.1007/s12011-012-9390-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Chromium Supplementation on Productive and Reproductive Performances and Some Metabolic Parameters in Late Gestation and Early Lactation of Dairy Cows

Abstract: The objective of this study was to determine the effect of supplemental chromium as chromium-L-methionine (Cr-Met) on productive and reproductive performances and some metabolic parameters in late gestation and early lactation of dairy cows. Sixty multiparous Holstein dairy cows according to prior lactation, parity, body mass (682±33 kg), and expected calving date were divided equally (30 cows/treatment) and were randomly allocated to one of the two groups. One group received basal diet without Cr (control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 62 publications
8
18
0
1
Order By: Relevance
“…Increased milk production was also reported by other researchers [5,9,10] in periparturient cows supplemented with 8, 6, and 5 mg/day Cr as Crmethionine (Cr-Met). Observations of a similar pattern were also reported by Nikkhah et al [24] and An-Qiang et al [45] in heat-stressed lactating cows supplemented with Cr-Met in the range of 0.05-0.10 mg Cr/kg of BW 0.75 and 0.2-0.6 mg Cr/day as Cr-picolinate, respectively.…”
Section: Productive Performancesupporting
confidence: 72%
See 2 more Smart Citations
“…Increased milk production was also reported by other researchers [5,9,10] in periparturient cows supplemented with 8, 6, and 5 mg/day Cr as Crmethionine (Cr-Met). Observations of a similar pattern were also reported by Nikkhah et al [24] and An-Qiang et al [45] in heat-stressed lactating cows supplemented with Cr-Met in the range of 0.05-0.10 mg Cr/kg of BW 0.75 and 0.2-0.6 mg Cr/day as Cr-picolinate, respectively.…”
Section: Productive Performancesupporting
confidence: 72%
“…Despite this, a positive effect of Cr supplementation on the insemination index, interval, and service period has been established [49,47] as well as a reduced incidence of endometritis and placental retention [50,51]. Kafilzadeh et al [10] reported that Cr supplementation increased the percentage of estrus behavior, percentage of cyclic cows, reduced day to first service, and day to first ovulation. They explained that reduced cortisol level and improved neutrophil count might be the reason.…”
Section: Reproductive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Burton et al (1993) reported increased cell-mediated immune response in periparturient and early lactating dairy cows supplemented with Cr. Furthermore, we and others have observed improved neutrophil count and activity with Cr supplementation (Lien et al, 2004;Kafilzadeh et al, 2012;Yasui et al, 2014;Horst et al, unpublished data). In agreement with the aforementioned literature, circulating neutrophils were increased in HSCr pigs by 37% relative to their HSCtl counterparts.…”
Section: Discussionsupporting
confidence: 61%
“…A similar result was also reported by KUMAR et al (2015), who found that the addition of inorganic Cr to heat-stressed buffalo calves influenced neutrophil phagocytic activity. Increased neutrophil phagocytic activity was also reported in Cr supplemented transition cattle (KAFILZADEH et al, 2012). However, no effect of dietary Cr supplementation on peripheral neutrophil phagocytic activity was reported by HALDAR et al (2009). The increase in humoral immune response in the 1.0 and 1.5 mg Cr/kg DM supplemented groups is consistent with the findings of KUMAR et al (2015) and DEKA et al (2014) who reported higher levels of TIg and IgG in Cr supplemented periparturient Murrah buffaloes and Murrah buffaloes calves, respectively.…”
Section: Discussionmentioning
confidence: 81%